1996
DOI: 10.1242/jeb.199.1.187
|View full text |Cite
|
Sign up to set email alerts
|

Landmark Stability: Studies Exploring Whether the Perceived Stability of the Environment Influences Spatial Representation

Abstract: To investigate whether spatial learning complies with associative learning theories or with theories of cognitive mapping, rats were trained in three experiments exploring the effect of variations in spatial predictive relationships. In experiment 1, it was found that making one of two landmarks the sole spatial predictor of reward, by varying the spatial relationship between reward and other cues, reduced the control over search exerted by that landmark compared with that observed when the landmark and contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
12
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(17 citation statements)
references
References 21 publications
5
12
0
Order By: Relevance
“…Some nutcrackers may have also used similar cues to locate the goal during the tests in which the apparatus was removed (see the Discussion section, Experiment 5). The finding is consistent with other work with nutcrackers (Gould-Beierle & Kamil, 1996) and rats (e.g., Biegler & Morris, 1996) in implicating the use of distal room cues during search. In Experiment 2, nutcrackers used local cues provided by the apparatus (e.g., the opening) to attempt to locate the goal.…”
Section: Discussionsupporting
confidence: 91%
“…Some nutcrackers may have also used similar cues to locate the goal during the tests in which the apparatus was removed (see the Discussion section, Experiment 5). The finding is consistent with other work with nutcrackers (Gould-Beierle & Kamil, 1996) and rats (e.g., Biegler & Morris, 1996) in implicating the use of distal room cues during search. In Experiment 2, nutcrackers used local cues provided by the apparatus (e.g., the opening) to attempt to locate the goal.…”
Section: Discussionsupporting
confidence: 91%
“…This ingenious disorientation procedure led Margules and Gallistel to the same conclusion drawn by Cheng, namely that rats failed to use the nongeometric information to correctly locate the target. These findings, and similar findings from other investigators (Biegler & Morris, 1993, 1996; Dudchenko, Goodridge, Seiterle, & Taube, 1997), provide further empirical data, showing that rats reoriented in accord with the shape of the environment but seemed to neglect nongeometric properties of the environment.…”
supporting
confidence: 90%
“…A more plausible explanation would be that these angular cues were not considered by the monkeys as stable or nonmovable. According to Biegler and Morris (1993, 1996), the relative stability of landmarks is an important factor in the development of spatial behaviors. It is generally thought that an object must be considered as immovable in order to be used as a landmark in navigation tasks (for an example with young children, see Acredolo, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with past research showing that proximal landmarks support route knowledge (e.g., Hurlebaus et al, 2008 ; Ruddle et al, 2011 ). Proximal landmarks provide local relative positional information (Benhamou & Poucet, 1998 ; Biegler & Morris, 1996 ) which is useful in route-based navigation tasks. Even though the presence of proximal landmarks in the training block significantly improved route learning, the relatively poorer performance of the PD compared to the D group in the transfer block suggested that the mere presence of the distal landmarks is not what facilitated successful route navigation, but rather the lack of proximal landmarks.…”
Section: Discussionmentioning
confidence: 99%